Exploring the therapeutic potential of essential oils: a review of composition and influencing factors - Abdelmohsen, Usama Ramadan; Elmaidomy, Abeer H. (Frontiers in Natural Products, 2025)
Essential oils (EOs) have a long-standing tradition and remain widely used in therapeutic applications. Their biological activities are primarily driven by complex interactions among their diverse components which exhibit synergistic or antagonistic effects, resulting in a broad spectrum of pharmacological and biological properties. These components are characterized by distinct molecular formulas, specific molecular weights, and unique physicochemical properties. The composition, content, and bioactivity of EOs are influenced by a variety of internal and external factors. Internal factors include genetic aspects (species, ecotype, chemotype, cultivar, and variety), plant developmental stage, and the specific plant part used. External factors encompass environmental and cultivation conditions (climate, radiation, diurnal and annual rhythms, harvesting practices, latitude, planting dates, irrigation, fertilization, salinity, and growth retardants), postharvest techniques (drying methods and storage conditions), and extraction and distillation processes (methods, moisture, acidity, distillation time, and gas chromatography analysis conditions). Additionally, oil degradation during storage (due to light, temperature, oxygen, chemical composition, and metal contaminants) and factors affecting bioactivity (plant part treated, solvent/detergent used, composition–activity relationships, techniques, biological material, dose/concentration selection, reference compounds, and comparison with literature data) play critical roles in shaping EO properties. This review provides a comprehensive examination of these factors, highlighting their impact on the content, composition, and bioactivity of EOs. By addressing these parameters in detail, this work aims to enhance the understanding of EOs and their therapeutic potential.